Classical philology in Belarus: main directions of research - Kirichenko, Arina V. (Journal of the Belarusian State University. Philology, 2024)
The main directions of scientific research carried out by the staff and graduates of the department of classical philology of the faculty of philology of the Belarusian State University are considered. The wide range of scientific interests of classical philologists is demonstrated: the implementation and study of translations into modern Belarusian language of texts of Roman and ancient Greek authors and Belarusian Latin-speaking writers of the Renaissance, consideration of the peculiarities of the functioning of phraseological units of ancient and biblical origin in Slavic languages, diverse analysis of existing Russian and Belarusian translations of New Testament texts, establishment of the word-formation potential of lexemes of Latin origin in Russian language, clarification of the possibilities of forming the terminology of linguistic poetics in Belarusian language, translation of Latin and ancient Greek non-equivalent vocabulary into Belarusian language, study of the reception of ancient mythology in modern literature and culture.